Evaluation of Noise Generated by Train Movement at Rail Near to Residential Areas – Case Study at Kluang, Johor. - Arbaan, Adilah; Ghing, Tong Yean; Othman, Mohd Hanifi; Yeung, David B. K. (International Journal of Sustainable Construction Engineering and Technology, 2022)
Rail transportation is one of the largest transportations that is widely used in Malaysia. Therefore, many railways have been built in urban and rural areas to improve interstate connectivity in Malaysia. However, train noise generated from train movement can disturb the comfort of nearby residents that live near railways. This study was conducted nearby the residential area between the Kluang – Renggam rail line to investigate the noise level and compare the existing noise level with the guideline from the Department of Environment (DOE) and World Health Organization (WHO) limits. The measurement data was taken by using the Sound Level Meter (SLM) type of SLM-25 at three different locations with distance of 20 m, 30 m, and 55 m away from the train track during morning, noon, and evening. The result shows the maximum value is 102.6 dBA during the evening at point 1 with a distance of 20 m. The residential area at point 1 which is 20 m distance between rail track and point 2 with the distance of 30 m from the rail track was indicated exposed to train noise disturbance whereby the measurement data for each location was exceeded the permissible noise for DOE and WHO which is 60 dBA and 54 dBA. The result can show that the noise level was dependent on the distance of the receiver to the train track. A better method such as developed noise mapping and the questionnaire of annoyance level for the residential area can improve the findings on the effect of train noise in the future.